(untitled) (University of Khartoum Engineering Journal, 2023)
Distributed solar photovoltaic (DSPV) is a practical and reliable solution in the case of Sudan, considering the vast and remote off-grid rural areas and the insufficient electricity generation in the parts powered by the national provider. This research outlines the scientific processes to work out the economic appraisal of an off-grid PV system with and without storage units that could be deployed within Greater Khartoum. The provided financial assessment, which relies on the PV price, the annualized monthly bill savings, the Levelized cost of energy, the simple payback period, and the national and regional kilowatt-hour tariffs, delivers an insight into the cost affordability of solar-generated electric power in Sudan. Accordingly, the analysis concluded that approximately 1.6 /Wp is the PV price for a system with a battery bank and 1.2 /Wp for the on-grid option, both to be fixed in the residential sector. However, the designed system here will not pay back the initial cost considering the low local electricity price. Also, considering the status quo, the investment will not attract investors in the energy sector, although it compensates for the frequent power deficiency in times of need. On the other side, the effort presents local experts and leaders in energy research and planning recommendations to encourage the governmental facilitation of DSPV use as viable renewable energy (RE) technological option. These recommendations hover around the issuance of country-level PV energy policies and are categorized into financial, policy, social, and technical. This work’s novelty is its contribution to developing and supporting the Sudanese literature in the energy field, in which the lack of resources and content specific to the republic, especially RE, is evident.